How to use… lymph node biopsy in paediatrics. Issue 5 (3rd May 2017) - Farndon, Sarah; Behjati, Sam; Jonas, Nico; Messahel, Boo
Abstract : Lymphadenopathy is a common finding in children. It often causes anxiety among parents and healthcare professionals because it can be a sign of cancer. There is limited high-quality evidence to guide clinicians as to which children should be referred for lymph node biopsy. The gold standard method for evaluating lymphadenopathy of unknown cause is an excision biopsy. In this Interpretation, we discuss the use of lymph node biopsy in children.